101 Shortened infusion of infliximab in 33 paediatric rheumatology patients. (December 2018) - Cheng, I; Aldous, B; Thoong, H; Pilkington, C
Abstract : Background: Infliximab has been associated with infusion-related reactions. In adults, infliximab can be administered at a shortened rate (over one hour). However, this practice has not been widely studied in the paediatric population. There is a change of practice at GOS whereby all patients on the rheumatology ambulatory ward who had tolerated at least four infliximab infusions given over two hours with no adverse effects were offered to have their infusions administered over one hour. Aims: To undertake a service evaluation to assess the tolerability of paediatric rheumatology patients receiving intravenous infliximab over 1 hour. The clinical records of all patients who were offered the shortened rate of infliximab infusion between June 2016 and March 2017 were reviewed retrospectively. Any acute adverse effects and delayed hyper-sensitivities reported up to May 2017 were documented. Results: 33 patients (aged between 6 to 15 years) received 159 infliximab infusions over one hour at 6 mg/kg every four to eight weeks. The number of infusions each patient received ranged from one to nine infusions (median=five). Of the 33 patients, six patients (18%) had infusion-related reactions, and when compared to the 15% in adult this is not statistically significant (Chi-squared test). Of the six patients, three patients (9%) had a cough/bronchospasms, one patient (3%) had facial rash and blister to arms, one patient (3%) had vomiting and flushing and one patient (3%) reported to have chest pain and headache. All symptoms resolved with or without pharmaceutical intervention. These six patients continued receiving the remainder of their doses over a total infusion time of two hours and received further doses over two hours thereafter without adverse effects. Conclusion: Paediatric patients with rheumatology conditions can tolerate intravenous infliximab over one hour. Repeat infusions were well tolerated and no delayed hypersensitivity-like reaction was reported post infusions.